THE MODERATING ROLE OF PROCUREMENT GOVERNANCE ON THE RELATIONSHIP BETWEEN SUPPLY CHAIN AGILITY AND SERVICE DELIVERY OF THE PUBLIC HEALTH CARE SECTOR IN THE COUNTY GOVERNMENTS OF WESTERN REGION, KENYA. - Mogere Kelvin Machuki; Evans Silver Kwendo; Nurwin Fozia (Research Collaboration Community (RCC), 2023)
Supply Chain Management is a crucial activity that entails overseeing the movement of materials form the source, throughput, to the end consumer. However, in this endeavour, there are increased instances of uncertainties i.e. speeds of delivery, flexibility and environmental factors that affect the services rendered to the end consumer. This drives the concept of supply chain agility which focuses on the speeds of response to any changes in the consumer demands. The healthcare sector has undergone significant changes within the past decades. Amidst these changes, attaining efficient and effective healthcare service delivery remains a distant prospect among multiple nations. This study therefore sought to find out the moderating role of procurement governance on the relationship between supply chain agility and service delivery in the Public health care sector in the county governments of the western region. The hypothesis for the study was: - Procurement Governance has no significant influence on the relationship between Supply Chain Agility and Service Delivery of the Public Health care sector in the County Governments of Western Region The study was anchored on three theories, theory of Human Service Delivery, Dynamic Capability Perspectives and Institutional Theory. The study adopted a Positivist research philosophy and a descriptive survey research design and the target population was 284 respondents of the four level 5 county hospitals in the western region. Questionnaires and interview schedules were used for data collection and analyzed using descriptive and inferential statistics. Data was presented using tables, scree plots and scatter plots.Â The study is of value to researchers and academicians, County government authorities and residents of the four counties. 258 respondents participated in the study and preliminary data checking, screening and cleaning was done. Validity and reliability statistics were done and they indicated that the research instruments were adequate for their purpose. Diagnostic tests were also conducted and none of the variables violated these assumptions. Regression analysis was done for the Supply Chain Agility and service delivery. Supply chain agility accounted for 44.5% of the changes in Service Delivery, but with the introduction of procurement governance as a moderator, the R2 value rose to 59.4% with pË‚0.05. This indicated that Procurement Governance was a significant moderator of the relationship. The study recommended that hospitals to should pay attention to three main aspects of procurement governance. First, they should set rules and policies that describe the authoritative position regarding the standards, principles, and objectives of the procurement process. Such standards include transparency and Accountability.